Enhancing Coffee Leaf Rust Detection with DenseNet201Plus and Transfer Learning - Karia, Adrian Jackob; Ally, Juma S; Leonard, Stanley (Universitas Bina Darma, 2025)
Coffee leaf rust (CLR) is a disease of coffee leaves caused by the fungus Hemileia Vastatrix, posing a major threat to global coffee production. Early and accurate detection is crucial for sustainable farming practices and disease management. This study proposes a novel deep learning approach that integrates DenseNet201Plus, an enhanced version of DenseNet201, with transfer learning to improve the accuracy and efficiency of CLR detection. DenseNet201Plus incorporates fine-tuned layers and optimized hyperparameters designed for plant disease classification, while transfer learning utilizes pre-trained weights from large-scale image datasets, enabling the model to adapt the characteristics of CLR images with limited training data. The model was evaluated on two datasets: the newly collected, high-quality Mbozi CLR dataset and the publicly available ImageNet CLR dataset, using accuracy, precision, recall, and F1-score. Results demonstrate that DenseNet201Plus achieved an accuracy of 99.0% on the Mbozi dataset, surpassing 97.78% obtained by the ImageNet Public dataset, with corresponding gains across all performance metrics. Results confirm that integration of DenseNet201Plus with transfer learning on the high-quality dataset significantly enhances CLR detection. The method outperformed several other baseline methods. The proposed approach offers a scalable, real-time detection solution for field deployment, supporting precision agriculture, enabling timely and targeted interventions.